2016
DOI: 10.1556/018.67.2016.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial evaluation of some novel sulfonylamido-benzoxazoles

Abstract: A series of 2-(p-substituted phenyl)-5-[(4-substituted phenyl) sulfonylamido]-benzoxazoles were synthesized and tested for their antimicrobial activities. The structures of the new derivatives were elucidated by spectral techniques. The minimum inhibitory concentrations (MIC) of the new benzoxazoles were determined against standard bacterial and fungal strains and drug-resistant isolates and compared to those of several reference drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Targeted compounds were synthesized treating 5-amino-2-(p-substitutedphenyl)benzoxazoles with appropriate p-substituted phenylacetylchlorides or p-substituted phenylsuphonylchlorides. [36][37] They reported that almost all the synthesized compounds exhibited good inhibitory activity to AChE and BChE enzymes, and moreover, they obtained activity close to that of the reference drug, galantamine. Compound 8a-m was a wide activity range with inhibition values of 6.80-90.21%.…”
Section: Benzimidazoles and Benzoxazoles In Alzheimer's Disease Treat...mentioning
confidence: 95%
See 1 more Smart Citation
“…Targeted compounds were synthesized treating 5-amino-2-(p-substitutedphenyl)benzoxazoles with appropriate p-substituted phenylacetylchlorides or p-substituted phenylsuphonylchlorides. [36][37] They reported that almost all the synthesized compounds exhibited good inhibitory activity to AChE and BChE enzymes, and moreover, they obtained activity close to that of the reference drug, galantamine. Compound 8a-m was a wide activity range with inhibition values of 6.80-90.21%.…”
Section: Benzimidazoles and Benzoxazoles In Alzheimer's Disease Treat...mentioning
confidence: 95%
“…synthesized a series of new benzoxazole rings and investigated the ChEI activity, since benzoxazoles are structural isosteres of natural nucleotides and easily interact with biopolymers. Targeted compounds were synthesized treating 5‐amino‐2‐(p‐substitutedphenyl)benzoxazoles with appropriate p‐substituted phenylacetylchlorides or p‐ substituted phenylsuphonylchlorides [36–37] . They reported that almost all the synthesized compounds exhibited good inhibitory activity to AChE and BChE enzymes, and moreover, they obtained activity close to that of the reference drug, galantamine.…”
Section: Benzimidazoles and Benzoxazoles In Alzheimer's Disease Treat...mentioning
confidence: 99%
“…The N2-N8 series was synthesized in our work following the procedure described in the literature, as shown in Figure 1 [22,23]. Initially, 5-Amino-2-(4-tert-butylphenyl)benzoxazole was obtained by reaction of 2,4-diaminophenol with 4-tert-butylbenzoic acid in PPA.…”
Section: Chemistrymentioning
confidence: 99%